MENTORING MODEL ELEMENTARY TEACHER PROFESSIONALISM THROUGH IMPROVED CLINICAL SUPERVISION IN DISTRICT GAJAHMUNGKUR SEMARANG CITY - Sulistyorini, Parmin, Umar Samadhy, Sri (Universitas Negeri Semarang, 2017)
Supervision clinics in order to fix and improving class teacher teaching skill. As leader and developer in the education institution, the supervisor, and head master professionalism as supervisor will give positive or negative impact through systematic aspects related to educations quality in the school they lead. The assumption is the supervisor and the head master professionalism will affect to the teacher professionalism. This research purpose is (1) To identify problems according to specification related with several needs of developing aspects supervision clinics, (2) Teacher guidance in the implementation of innovative study in the teaching process, (3) Teacher guidance at commander and the head master in preparing supervision clinics, (4) Describing and analyzing the commander and the head master skills in supervision clinics implementation. The research subject is the commander, head master, and teachers in the elementary of UPTD Education Sub District of Gajahmungkur. The data collecting was done by interviewing technique, observation, and documentation. The data analysis was done as descriptive qualitative. In this research produced several documents supervision clinics support which is in the form of guidance instruments interviewing of pre observation, the observation instruments of the study and the guidance instruments interviewing after observation, and RPP (Lesson Plan). After guidance at the steps of clinics supervision which is contain of first meeting (preconference), observation study, and giving reinforcement (reinforcement) to the teachers. In the implementation of teacher teaching and learning process was implemented innovation study which is study focusing at the students, it is good news for the students who active to follow the study.